Progress in the preparation and application of CsPbX3 perovskites. Issue 10 (27th April 2022) - Pan, Yingwen; Zhang, Yaofang; Kang, Weimin; Deng, Nanping; Yan, Zirui; Sun, Wei; Kang, Xiaoying; Ni, Jian
Abstract : In this review, recent progress on the preparation and application of CsPbX3 perovskites is outlined. Abstract : In recent years, organic–inorganic metal halide (OIH) perovskites have become a popular material of increasing interest. Due to the presence of organic cations, OIH perovskites suffer from chemical instability and easy decomposition in harsh environments with high temperature and humidity. All-inorganic perovskites have better stability compared to OIH perovskites. Due to the intensive research and continuous optimization of the preparation process, the power conversion efficiency (PCE) of all-inorganic perovskite solar cells (PSCs) has exceeded 20%. Therefore, all-inorganic CsPbX3 (X = Br, I, CI) perovskites are becoming popular and are potential materials suitable for optoelectronic devices. CsPbX3 perovskites exhibit many excellent physical and optical properties, such as high carrier mobility and high fluorescence. In this review, recent progress on the preparation and application of CsPbX3 perovskites is outlined. Firstly, the physical structure and excellent optical properties of CsPbX3 perovskites are briefly described. Next, the preparation of different morphologies of CsPbX3 perovskites is described. Furthermore, this paper summarizes the application of CsPbX3 in optoelectronic devices, including PSCs, light-emitting diodes (LEDs), and photodetectors (PDs). The performance parameters of CsPbX3 devices are summarized. Finally, a brief summary of the full paper is presented and the challenges facing the field of all-inorganic CsPbX3 perovskites are discussed.